2017
DOI: 10.1242/jeb.145763
|View full text |Cite
|
Sign up to set email alerts
|

Role of the different eyes in the visual odometry in the wolf spider Lycosa tarantula (Araneae, Lycosidae)

Abstract: The wolf spider Lycosa tarantula returns home by means of path integration. Previous studies demonstrated: (i) that the angular component of the outbound run is measured using a polarized-light compass associated with the anterior median eyes; (ii) changes in direction of the substratum are detected by the anterior lateral eyes (ALEs); and (iii) in relation to the linear component of the outbound run, an increase of optic flow, in either the lateral or ventral fields of view, caused spiders to search for the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…PI is well documented for many animals, but the studies of desert ants are the most extensive (Wehner, 1992; Wehner and Srinivasan, 1981; Wehner et al, 1996; 2004; 2006; Wolf, 2011; Wittlinger et al, 2006; 2007; Wittlinger and Wolf, 2013; Heinze et al, 2018; Srinivasan, 2015; Wittlinger et al, 2006; Wolf, 2011). PI has also been described for some groups of spiders (Ortega-Escobar, 2002; 2006; Ortega-Escobar and Ruiz, 2017; 2014; Görner and Claas, 1985; Moller and Görner, 1994; Seyfarth and Barth, 1972; Seyfarth et al, 1982), and a recent study showed evidence of path integration in the lesser Asian scorpion, Mesobuthus eupeus (Prévost and Stemme, 2020).…”
Section: Introductionmentioning
confidence: 83%
“…PI is well documented for many animals, but the studies of desert ants are the most extensive (Wehner, 1992; Wehner and Srinivasan, 1981; Wehner et al, 1996; 2004; 2006; Wolf, 2011; Wittlinger et al, 2006; 2007; Wittlinger and Wolf, 2013; Heinze et al, 2018; Srinivasan, 2015; Wittlinger et al, 2006; Wolf, 2011). PI has also been described for some groups of spiders (Ortega-Escobar, 2002; 2006; Ortega-Escobar and Ruiz, 2017; 2014; Görner and Claas, 1985; Moller and Görner, 1994; Seyfarth and Barth, 1972; Seyfarth et al, 1982), and a recent study showed evidence of path integration in the lesser Asian scorpion, Mesobuthus eupeus (Prévost and Stemme, 2020).…”
Section: Introductionmentioning
confidence: 83%
“…PI is well documented for many animals, but the studies of desert ants are the most extensive ( Collett, 2019 ; Wehner, 1992 ; Wehner and Srinivasan, 1981 ; Wehner et al, 1996 , 2004 , 2006 ; Wolf, 2011 ; Wittlinger et al, 2006 , 2007 ; Wittlinger and Wolf, 2013 ; Heinze et al, 2018 ; Srinivasan, 2015 ). PI has also been described for some groups of spiders ( Ortega-Escobar, 2002 , 2006 ; Ortega-Escobar and Ruiz, 2014 , 2017 ; Görner and Claas, 1985 ; Moller and Görner, 1994 ; Nørgaard, 2005 ; Seyfarth and Barth, 1972 ; Seyfarth et al, 1982 ), and a recent study showed evidence of PI in the lesser Asian scorpion, Mesobuthus eupeus ( Prévost and Stemme, 2020 ).
Fig.
…”
Section: Introductionmentioning
confidence: 84%
“…Wolf spiders may be capable of using idiothetic and allothetic information simultaneously or perhaps hierarchically to integrate orientation information. Ortega‐Escobar and Ruiz (2017) found that during path integration navigation, wolf spiders use the anterior median eyes to navigate via a polarized light compass and use other sets of eyes as visual odometers to record distance. Polarized light navigation could be construed as a type of orientation cue and, therefore, regarded as a landmark.…”
Section: Discussionmentioning
confidence: 99%